1995
DOI: 10.1021/bi00014a032
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Blood Group Lewis b Determinant from Lewis a: Association of this Novel .alpha.(1,2)-L-Fucosylating Activity with the Lewis Type .alpha.(1,3/4)-L-Fucosyltransferase

Abstract: Blood group H type 1 [Fuc alpha (1,2)Gal beta (1,3)GlcNAc beta-->] is known as the precursor structure of the blood group determinant, Lewis b [Fuc alpha (1,2)Gal beta (1,3)(Fuc alpha (1,4))GlcNAc beta-->]. Recently, a new biosynthetic route for Lewis b from Lewis a [Gal beta (1,3)(Fuc alpha (1,4))GlcNAc-->] was identified in human gastric carcinoma cells, colon carcinoma Colo 205, and ovarian tumor. The present study demonstrates the association of this new type of alpha (1,2)-L-fucosyltransferase (FT) activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 15 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…the genetic origin of this 'aberrant' α(1,2)Ft is still unclear. Initially assumed to be a result of Se gene modulation during cancer transformation, it presently appears to be associated with the FUT3 gene that encodes the α(1,3/4)Ft lewis enzyme (25).…”
Section: Discussionmentioning
confidence: 99%
“…the genetic origin of this 'aberrant' α(1,2)Ft is still unclear. Initially assumed to be a result of Se gene modulation during cancer transformation, it presently appears to be associated with the FUT3 gene that encodes the α(1,3/4)Ft lewis enzyme (25).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that Le b biosynthesis in non-secretors takes place via A1,2 fucosylation of Le a has been proposed [23], and the authors suggested the existence of an, as yet unidentified, aberrant, A1,2FT in cancer cells [23]. A recent report proposed that such Le a acting activity is Fuc-TIII in COLO-205 cells [38]. Transfection experiments [24] and transgenic mice expressing Fuc-TIII [25] demonstrated that this enzyme promotes synthesis of both type 1 and 2 antigens (including SLe x).…”
Section: Discussionmentioning
confidence: 99%
“…However, Le b antigen levels in the plasma of the se2/se2 genotype were also high, and this results conflicts with the biosynthetic pathway. Another route by which the Le b antigen is biosynthesized from Le a antigen in colorectal carcinoma [29] and in gastric carcinoma and ovarium tumor [30] has been reported. This route might be related to the production of the Le b antigen in cord plasma (se2/se2).…”
Section: Discussionmentioning
confidence: 99%